Exegesis is a game - Roux, Jurie le (HTS teologiese studies, 2019)
Eben Scheffler’s understanding of Luke 24:13–33 enabled us to understand the exegesis of the Old Testament of the past two millennia as a play with words, expressions and interpretations. According to Luke, the suffering of the community can be alleviated when the Old Testament is studied because they would once again experience the presence of Christ and would be filled with joy. This is exactly what happened since the early church up to now. The Old Testament has been read and preached and God’s presence experienced, but it is important to note that up to now no fixed method has been designed or a final message has been formulated. This can be ascribed to our finiteness, and therefore it is suggested that we must rather speak of exegesis as a play (as formulated by Hans-Georg Gadamer) instead of depicting it as a scientific method comprising definite steps which must be applied in a strict way to identify and describe eternal truths.